2009
DOI: 10.1299/jamdsm.3.236
|View full text |Cite
|
Sign up to set email alerts
|

On the Synthesis of Spatial RRSS Motion Generators with Prescribed Coupler Loads

Abstract: This work extends the concepts and methodologies of Shen et al (1) and Al-Smadi et al (2) to synthesis of spatial RRSS motion generators with applied coupler loads. A general four-bar mechanism constraint that includes a coupler static load and a driver static torques is formulated using the principal of virtual work. This constraint is combined with the conventional RRSS motion generation model by Suh and Radcliffe (13) to form a nonlinear optimization problem from which RRSS mechanism solutions are calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Russell et al presented an RRSS motion generation model that includes prescribed coupler forces (8) .…”
Section: Published Work On Rrss Mechanism Analysis and Synthesismentioning
confidence: 99%
“…Russell et al presented an RRSS motion generation model that includes prescribed coupler forces (8) .…”
Section: Published Work On Rrss Mechanism Analysis and Synthesismentioning
confidence: 99%
“…Such optimization models have already been introduced for the 4 Revolute Spherical (or 4R Spherical) linkage, the Revolute-Revolute-Spherical-Spherical (or RRSS) linkage and the Revolute-Revolute-Spherical-Cylindrical (or RRSC) linkage. 1417 No such optimization model has been presented for the RCCC linkage until now.…”
Section: Introductionmentioning
confidence: 99%
“…From a kinematics point of view, a suspension system can be defined as a combination of links and joints (Russell, et al, 2009), (Tanık and Parlaktaş, 2011), (Tanık and Parlaktaş, 2015c) A double wishbone mechanism is essentially a RSSR-SSP (R:revolute, S:spherical, P:prismatic) linkage (Shen, et al, 2014) when steering function is required as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%